2017
DOI: 10.32929/2446-8355.2017v26n1p10-20
|View full text |Cite
|
Sign up to set email alerts
|

Reaproveitamento Do Resíduo Da Indústria De Carnaúba No Substrato Para Produção De Mudas De Melancia

Abstract: Os produtores de mudas de hortaliças estão sempre ávidos por novas tecnologias, especialmente quando se trata do insumo substrato para plantas. Neste sentido, objetivou-se avaliar o desenvolvimento de mudas de melancia cultivar Crimson Sweet, produzidas em diferentes proporções de resíduo de carnaúba para composição de substratos. O experimento foi conduzido em delineamento experimental inteiramente casualizado com cinco tratamentos com diferentes proporções de resíduo de carnaúba com casca de arroz (RCCA) e r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…The carnauba bagana is normally used as mulch and organic fertilizer for the carnauba trees themselves in Northeastern Brazil. Recent studies have demonstrated its viability in vegetable plantations (Souza et al, 2016;Gomes et al, 2020) and in the composition of substrates for the production of seedlings (Albano et al, 2017;Silva et al, 2017). The use of mulch has as one of the main benefits the reduction of water loss from the soil through evaporation, due to protection against direct insolation and reduction of soil temperature, important factors to promote plant development, especially in semi-arid regions such as the Brazilian Caatinga (Macêdo, 2007;Gomes et al, 2009;Silva et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The carnauba bagana is normally used as mulch and organic fertilizer for the carnauba trees themselves in Northeastern Brazil. Recent studies have demonstrated its viability in vegetable plantations (Souza et al, 2016;Gomes et al, 2020) and in the composition of substrates for the production of seedlings (Albano et al, 2017;Silva et al, 2017). The use of mulch has as one of the main benefits the reduction of water loss from the soil through evaporation, due to protection against direct insolation and reduction of soil temperature, important factors to promote plant development, especially in semi-arid regions such as the Brazilian Caatinga (Macêdo, 2007;Gomes et al, 2009;Silva et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…In the Potiguar basin, carnaúba bagana is a locally available material that can be used as mulch in environmental restoration plantations. This industrial organic residue is derived from the extraction of wax from the leaves of the carnaúba palm tree (Copernicia prunifera [Miller] H) (Ferreira et al, 2013;Silva et al, 2017). Farmers in regions where carnaúba wax is produced commonly use this residue due to its low-cost and efficient ground-covering properties (Queiroga et al, 2002).…”
Section: Introduction and Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…O resíduo da bagana de carnaúba é abundante nas regiões de ocorrência dessa palmeira e utilizado com sucesso nas diversas etapas do desenvolvimento das mudas, desde a germinação até o estabelecimento em campo. No entanto, tem ocupado lugar de destaque na composição de substratos, sendo recomendado por diversos autores (SOUSA et al, 2012;ALBANO et al, 2017;SILVA et al, 2017).…”
Section: Metodologiaunclassified